2020
DOI: 10.1371/journal.pntd.0008291
|View full text |Cite
|
Sign up to set email alerts
|

Impact of common skin diseases on children in rural Côte d’Ivoire with leprosy and Buruli ulcer co-endemicity: A mixed methods study

Abstract: Background Skin-related neglected tropical diseases (skin NTDs) occur against a background of a very high prevalence of common skin diseases in sub-Saharan Africa. In this study, we examined the knowledge, attitude and practices (KAP) and the impact of common skin diseases in children living in a leprosy and Buruli ulcer (BU) co-endemic district in a west African country of Cô te d'Ivoire, in order to help inform disease control efforts for skin NTDs. Methods and principle findings Fourteen focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…In a study conducted in West Africa, a modified Children’s Dermatology Life Quality Index Questionnaire was used and Focused Group Discussions were conducted to investigate the impact of common skin diseases on school children. Social relationships were often affected, wherein children having skin diseases were mocked, rejected or isolated causing affective changes as well as behavioral changes, such as isolation, self-restraint and self-stigma [ 30 ]. Our study revealed that the economic effect of yaws was another obvious difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in West Africa, a modified Children’s Dermatology Life Quality Index Questionnaire was used and Focused Group Discussions were conducted to investigate the impact of common skin diseases on school children. Social relationships were often affected, wherein children having skin diseases were mocked, rejected or isolated causing affective changes as well as behavioral changes, such as isolation, self-restraint and self-stigma [ 30 ]. Our study revealed that the economic effect of yaws was another obvious difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…These are usually circular in shape with numerous broken-off hairs as well as fine scaling, which characteristic features also observed in our cases [ 1 , 14 ]. Unlike M. canis or M. gypseum infections, there is usually no pruritus [ 1 , 14 ], which might in part account for the lack of requests for medical attention [ 5 ], and likelihood of spreading the disease from untreated cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is most prevalent in children in developing countries, affecting mostly persons of low socio-economic status [ 1 , 2 , 3 , 4 ]. However, the reported prevalence is likely an underestimation as the conditions are often neglected or ignored due to the non-fatal nature compared to other health issues prevalent in settings where they are endemic [ 5 ]. There is also a paucity of laboratories capable of performing mycological examinations, so diagnostic confirmation is rarely done [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of skin diseases is high in sub-Saharan Africa, particularly in children, and the reported prevalence ranges from 23.3% to as high as 80.4% in this age group [ 1 - 7 ]. These diseases are most often overlooked due to a lack of local specialists and lack of experience among Western specialists looking at darker skin [ 8 ]. However, if left untreated, even some of the most common skin diseases could have severe complications (eg, scabies could lead to rheumatic fever and nephropathy, as well as often debilitating physical, social, and mental effects that may deprive one of educational and social opportunities [ 9 , 10 ]).…”
Section: Introductionmentioning
confidence: 99%